"Análisis de ensayos de procedencia-progenie de (Dipteryx panamensis (Pittier) Record & Mell), en la Zona Norte y Sur de Costa Rica." - León-Fallas, Natalia (Instituto Tecnológico de Costa Rica, 2014)
Almendro (Dipteryx panamensis) is a native tree species with a wide natural distribution from Costa Rica and throughout Amazons basin. It is known by its high ecological value explained by the importance of its seeds, as a food source for a large fauna. This leguminous tree has been planted and investigated in Costa Rica since late 80’s until today, well known for its high wood density. Due to its wood valuable potential, GENFORES (Forest gene conservation and breeding cooperative) initiated a tree improvement program, as a development strategy to promote its utilization as an attractive crop option in low and wet lands in the American tropics. The objective of this study was to evaluate two provenanceprogeny tests established 4 years ago in north zone (San Carlos) and southern Pacific Costa Rica (Osa, peninsula). Materials came from three native provenances (Puerto Viejo, Sarapiquí; Crucitas, San Carlos and San Marcos, San Carlos) and 10 open-pollinated families within each provenance. Results showed no significant differences among provenances in any of the traits evaluated, which suggests focusing on best families. If operational plantations are established with the seed collected from the four best trees, within the top five-ranking families, genetic gain in wood commercial volume per tree would increase more than 45% at age 4. Genetic correlations among both sites registered values over 90%, which reflects a high genetic stability and the possibility of a single national breeding program for this tree species.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2014.
Keywords: Polinización; Semilla; Ambiente; Suelo; Plantación de bosques